Well-defined functional mesoporous silica/polymer hybrids prepared by an ICAR ATRP technique integrated with bio-inspired polydopamine chemistry for lithium isotope separation. Issue 18 (24th April 2017) - Liu, Yuekun; Liu, Xuegang; Ye, Gang; Song, Yang; Liu, Fei; Huo, Xiaomei; Chen, Jing
Abstract : Mesoporous silica/polymer hybrids synthesized via polydopamine-assisted surface-initiated ICAR ATRP for lithium isotopes separation. Abstract : Mesoporous silica/polymer hybrids with well-preserved mesoporosity were prepared by integrating the initiators for continuous activator regeneration (ICAR) atom transfer radical polymerization (ATRP) technique with the bio-inspired polydopamine (PDA) chemistry. By manipulating the auto-oxidative polymerization of dopamine, uniform PDA layers were deposited on the surfaces and pore walls of ordered mesoporous silicas (OMSs), thereby promoting the immobilization of ATRP initiators. Poly(glycidyl methacrylate) (PGMA) brushes were then grown from the OMSs by using the ICAR ATRP technique. The evolution of the mesoporous silica/polymer hybrids during synthesis, in terms of morphology, structure, surface and porous properties, was detailed. And, parameters influencing the controlled growth of polymer chains in the ICAR ATRP system were studied. Taking advantage of the abundant epoxy groups in the PGMA platform, post-functionalization of the mesoporous silica/polymer hybrids by the covalent attachment of macrocyclic ligands for the adsorptive separation of lithium isotopes was realized. Adsorption behavior of the functionalized hybrids toward lithium ions was fully investigated, highlighting the good selectivity, and effects of temperature, solvent and counter ions. The ability for lithium isotope separation was evaluated. A higher separation factor could be obtained in systems with softer counter anions and lower polarity solvents. More importantly, due to the versatility of the ICAR ATRP technique, combined with the non-surface specific PDA chemistry, the methodology established in this work would provide new opportunities for the preparation of advanced organic–inorganic porous hybrids for broadened applications.